(untitled) (Research, Society and Development, 2022)
As part of the emerging challenge of finding ways to carry students/citizens to the development of science education, the term Scientific Literacy (SL) from English literature, or Alfabetización Científica (AC), from Spanish studies, have been mentioned by several brazilian authors, sometimes to designate the same context, in others, to make a distinction, And in the documents governing the Student Assessment Program (PISA), which provides information on the performance of students aged 15 years, is this issue addressed? This question also extends to the National Curricular Common Base (BNCC), a mandatory reference for the elaboration of school curricula and pedagogical proposals for all levels of education. In this way, due to the polysemy that has surrounded the use of these words, we believe this research is necessary in order to understand the concepts that are attributed to them, in which contexts they are used and, from this, select the one that best fits in our studies in the field of Science. This investigation has a qualitative character and, as for the procedure, we will make use of bibliographic research. In view of the conceptions found, we chose to use the term Alfabetización Científica, from Sasseron’s perspective, since we agree with the author’s view, although it is necessary to take into account that, in official documents, which govern teaching in basic education, and in learning assessment programs, the term Scientific Literacy is adopted.